Pathological Locomotor Phenomena in the Wrist Joint Associated with Transposition of the Pronator Teres at Dysfunction of the Muscles of the Posterior Surface of the Forearm Caused by Denervation Process of Traumatic Genesis - Hatskyi, O.O.; Tretiak, I.B.; Tsymbaliuk, V.I.; Bazik, O.M.; Tsymbaliuk, Ya.V. (TERRA ORTHOPAEDICA, 2021)
Relevance. Dysfunction of the muscles of the posterior surface of the forearm leads to loss of extension in the wrist joint, metacarpophalangeal joints, and loss of abduction and extension of the first finger. The cause of dysfunction is damage to the radial nerve, supraclavicular or subclavian damage to the brachial plexus. The long regeneration process makes it impossible to effectively use the injured limb for a long period of time. Palliative use of movements (transposition) of muscles can significantly reduce the time for the patient to return to active use of the injured limb. Each of the muscle transpositions has certain disadvantages associated with the development of pathological locomotor phenomena (PLF) in the wrist joint. Ways to overcome them are based on a purely mechanistic approach, which is most often simplified to change the point of attachment of the primary non-functioning effector muscles. Objective: to define most adequate complex surgical approach in restoring effective extension function in the wrist joint and metacarpophalangeal joints. Materials and Methods. A retrospective analysis of the surgical treatment of 30 consecutive cases of dysfunction of the muscles of the posterior surface of the forearm caused by traumatic damage to the structures of the peripheral nervous system (PNS) of various localization was carried out. 23 patients with damage to the radial nerve. 7 patients with pathology of the brachial plexus. The mean age of patients was 41 years (from 18 to 64 years). Mean terms to primary surgical treatment were 4.6 months. 7 patients underwent only revision of the radial nerve within the segment (defect >10 cm); 6 patients underwent neurotization of the posterior interosseous nerve using the Mackinnon technique; 5 patients underwent autologous plasty of the radial nerve (defect <10 cm); 5 patients underwent its neurolysis. Neurolysis was performed in 6 patients with pathology of the brachial plexus, neurotization of the posterior interosseous nerve was performed in 1 case using the Mackinnon method. All patients underwent transposition of the forearm pronator teres (PT) according to the standard technique. Twelve patients underwent transposition of the flexor carpi radialis muscle (FCR, 4 cases) or flexor carpi ulnaris (FCU, 8 cases) according to the standard technique. The results of transposition were analyzed after 1 month or later than 6 months, using a clinical neurological method. Regeneration of neural structures of PNS were analyzed within 9-12 months and additionally in terms later than 15 months both neurologically and electrophysiologically. Results. In 6 patients, there was no restoration of extension in the metacarpophalangeal joints (EMPJ), in 12 patients there was a complete recovery of EMPJ after interventions on the structures of the PNS (4 cases – autologous plasty, 7 cases – distal neurotization, 1 case – neurolysis of the radial nerve). In 8 patients, the formation of PLF was not observed during extension in the wrist joint after muscle transposition. In 15 patients, PLF “type B” was formed, and in 7 patients, PLF “type C” was formed within 1 month after muscle transposition. In none of the patients, PLF “type C” was observed to be preserved for >6 months. In 8 patients, a permanent PLF “type B” was formed, which in 4 cases transformed into PLF “type D”. The formation of a steady-state PLF “type D” was recorded in all cases of neurolysis of the PNS structures without restoring extension in the metacarpophalangeal joints by the method of transposition. The formation of a steady-state PLF “type B” was recorded in all cases of FCU transposition to restore extension in the metacarpophalangeal joints. In 11 cases of reduction in the primary function of the FCR as a result of its denervation (neurotization according to the Mackinnon method) or transposition of the FCR muscles (change in the primary attachment point), PLF “type B” did not develop. Conclusions. Based on the results of the study, it was found that the most adequate complex surgical approach to avoid the formation of a stable PLF caused by muscle transposition to restore extension in the wrist joint is Mackinnon neurotization or FCR transposition to restore EMPJ.